Truth by analysis games, names, and philosophy - McGinn, Colin, 1950- (New York : Oxford University Press, 2012)
In this study of the nature of philosophy, Colin McGinn shows us how philosophy can maintain its connection to the past while looking forward to a bright future.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references.
Keywords: Philosophy; Analysis (Philosophy)